c-myc gene amplification during hepatocarcinogenesis by a choline-devoid diet. - Chandar, N (1989)
Liver tumors arise in rats fed a choline-devoid diet without added carcinogens. We found amplification of the c-myc gene in 13/13 of these tumors. The amplification ranged from 2- to 70-fold and was accompanied by an increase in c-myc gene expression. Amplification of c-myc was larger in tumors of rats fed a choline-devoid diet followed by a choline-supplemented diet than in tumors from animals fed a choline-devoid diet exclusively. In the former animals, low levels of c-myc gene amplification were also detected in nontumorous regions of tumor-bearing livers. The choline-devoid diet provides an in vivo experimental model for the induction of gene amplification in the rat liver. In this setting, amplification of the c-myc gene may be an early and critical event in carcinogenesis.